Preference of Bactrocera spp. to methyl eugenol based different coloured traps - BAJAJ, KAVITA; SINGH, SANDEEP (The Indian Journal of Agricultural Sciences, 2020)
Fruit flies, Bactrocera dorsalis (Hendel) and Bactrocera zonata (Saunders) are highly destructive pests of peach, pear, guava and Kinnow mandarin causing up to 80, 70, 100 and 60-80% fruit infestation, respectively. These fruit flies are very difficult to manage due to the fact that they are polyphagous, multivoltine adults have high mobility and fecundity and all the development stages are unexposed. Males of Bactocera spp. are highly attracted toward parapheromone methyl eugenol. Studies on the response of fruit flies to methyl eugenol based different coloured PAU fruit fly traps (red, green, yellow and standard transparent trap) were carried out in peach, pear, guava and Kinnow orchards during 2016-17. The result showed that yellow trap was consistently the most attractive as compared to other trap colours in all the four crops. The use of yellow coloured fruit fly traps can help in attracting more fruit flies, thereby reducing their population in the respective orchards.